Acute effects of phenylbutyrate on glutamine, branched‐chain amino acid and protein metabolism in skeletal muscles of rats - Holecek, Milan (Int J Exp Pathol, 2017)
Phenylbutyrate (PB) acts as chemical chaperone and histone deacetylase inhibitor, which is used to decrease ammonia in urea cycle disorders and has been investigated for use in the treatment of a number of lethal illnesses. We performed in vivo and in vitro experiments to examine the effects of PB on glutamine (GLN), branched‐chain amino acid (BCAA; valine, leucine and isoleucine) and protein metabolism in rats. In the first study, animals were sacrificed one hour after three injections of PB (300mg/kg b.w.) or saline. In the second study, soleus (SOL, slow twitch) and extensor digitorum longus (EDL, fast twitch) muscles were incubated in a medium with or without PB (5 mM). L‐[1‐(14)C] leucine was used to estimate protein synthesis and leucine oxidation, and 3‐methylhistidine release was used to evaluate myofibrillar protein breakdown. PB treatment decreased GLN, BCAA and branched‐chain keto acids (BCKAs) in blood plasma, decreased BCAA and increased GLN concentrations in muscles, and increased GLN synthetase activities in muscles. Addition of PB to incubation medium increased leucine oxidation (55% in EDL, 29% in SOL), decreased BCKA and increased GLN in medium of both muscles, increased GLN in muscles, decreased protein synthesis in SOL and increased proteolysis in EDL. It is concluded that PB decreases BCAA, BCKA and GLN in blood plasma, activates BCAA catabolism and GLN synthesis in muscle and exerts adverse effects on protein metabolism. The results indicate that BCAA and GLN supplementation is needed when PB is used therapeutically and that PB may be a useful prospective agent which could be effective in management of maple syrup urine disease.